Classification and Nomenclature of Metacaspases and Paracaspases: No More Confusion with Caspases - Minina, Elena A. (2020)
Fil: Minina, Elena A.. Swedish University of Agricultural Sciences and Linnean Center for Plant Biology; Suecia